Analisis Kualitas Pelayanan Indomaret Menggunakan Model SERVQUAL di Kota Tanah Grogot - S, Fathur Rahman; Nuraini, Nuraini; Prihatin, Titiek Aryati; Aswan, Aswan (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of service quality on consumer satisfaction of indomaret in the city of Tanah Grogot. A quantitative approach was used by collecting data through questionnaires to 75 selected respondents using accidental sampling techniques. Service quality measurement also refers to SERVQUAL's five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Data analysis was carried out using multiple linear regression with the help of jamovi. The results of the study show that simultaneously all dimensions of SERVQUAL have a significant effect on consumer satisfaction. Partially, the variables of reliability, responsiveness, assurance, and empathy had a significant effect, while tangibles had no significant effect. The value of the determination coefficient indicates that most of the variation in consumer satisfaction can be explained by this research model. These findings are expected to be a consideration for retail managers in improving service quality.